ANALISIS IMPLEMENTASI DAN UPAYA PENANGGULANGAN KEJADIAN KEBAKARAN DI TOWER KENANGA APARTEMEN MEDITERANIA GARDEN RESIDENCE 2 TAHUN 2020 - Mutiara Sonia Syafitri (2021)
Tower Kenanga Mediterania Garden Residence 2 Apartment is a residential building. The safety factor is an important considered aspect because it is closely related to the designation of the building and the safety of its users, specifically the fire safety aspect. This study aims to find out the conformity of implementation at the Tower Kenanga Mediterania Garden Residence 2 Apartment about active protection system, lifesaving facilities, and organizing as part of fire mitigation efforts. This research used a descriptive study design with a qualitative approach. Data collection by observation with checklist sheets, in-depth interviews, and reviewing documents, compared the collected data with the applicable rules and standards in Indonesia and determined the level of conformity. The results showed Tower Kenanga Mediterania Garden Residence 2 Apartment has an active protection system conformity rate of 91.67%, life-saving facilities 88.1%, and organizing 100%, which indicates that three components of fire mitigation in the Category Good (B). But there are still some components that must be equipped, the results of this study suggest adding APAR marks, labeling hydrants, providing backup sprinklers and sprinkler locks, excitable lines that are not obstructed objects, adding directions, installation of emergency stair rails on both sides, inspection, maintenance, testing, and things to do in fulfilling of fire implementation and efforts.